Effects of pulsed electric fields on exciton propagation efficiency along Müller cell intermediate filaments. Possible separation mechanism of high- and low-contrast images by the eye-brain system - Khmelinskii, Igor (2022)
In the current study, we tested a possible mechanism of low-and high-contrast image component discrimination by the vertebrate eye-brain system. Apparently the eye-brain system has to discriminate between the low-contrast image component formed by light scattered within the retina, due to interaction of photons with cells and their parts, and the high-contrast image component transmitted by excitons via the quantum mechanism. Presently, effects of pulsed electric fields applied to Muller cell (MC) intermediate filaments (IFs) on the efficiency of exciton propagation were explored. The effects of both pulse duration and amplitude were recorded. These experimental results show that the eye-brain system may be using signal modulation to discriminate between high-and low-contrast image components, improving our understanding of high-contrast vision in vertebrates.